Liquid biofuels: emergence, development and prospects - Silveira dos Santos, Manoela; Benedetti Santos, Omar Inácio; Borenstein, Denis; Domingos Padula, Antonio (Lecture Notes in Energy, 2014)
Bioenergy is coming to be seen as a priority on the international agenda, with the use of liquid biofuels a key strategy in the attempt to meet both the demand for environmental sustainability and the energy needs of countries. The growth in the production and use of biofuels around the world has led to increased interest and discussion about this subject. Given the dynamics of this phenomenon, the organizers of this book, based on more than 10 years experience of joint research on this subject, seek to address key issues relating to the production and marketing of liquid biofuels using the Brazilian experience with ethanol and biodiesel as an illustrative case, as well as the experiences of the leading producers and consumers of biofuels. The topics to be covered in this book include the role of public policies in fostering the emergence of the biofuels industry, the main socio-economic, environmental, technological aspects and the prospects for the sector. The conceptual and methodological bases that provide analytical support to the book are based on recent research published in indexed journals. The structure and content of the book seek to address some central issues regarding: How the biofuel industries have emerged and developed in different countries? What factors have been crucial to the success or failure of different production initiatives? What are the main socio-economic-environmental impacts of the production and consumption of liquid biofuels? How are national and international markets for liquid biofuels being structured? To what extent and/or in what conditions can the experiences and lessons learned at the national level be transferred and adapted in other countries? Finally, based on the scenarios, the prospects for liquid biofuels will be discussed.